PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI IPA SMAN 1 KECAMATAN LAREH SAGO HALABAN - Yendri Susanti (Jurnal Edukasi dan Penelitian Matematika, 2022)
One of the learning objectives in mathematics that must be mastered by students is understanding mathematical concepts. from field observations, ityis knownmthat the understanding of mathematics concepts for classdX IPA SMANd1 Kecamatan LarehgSago Halabanhin the 2020/2021 academic year is low. Applying therProblem Based Learning learning modelkin the learningkprocess is expected to improve student’s understandingoof mathematical concepts.gThis research aimsgto describe whether the understanding of mathematical concepts of students who learn to apply the Problem Based Learning modelois betterothan the understandingoof mathematicaloconcepts of studentsowho learnoby applyingodirect learning models in class XI IPA SMAN 1 Kecamatan Lareh Sago Halaban. This research belongs to the type ofoquasi-experimental research with a static group design.oThe population used is class XI IPA SMAN 1 Kecamatan Lareh Sago Halaban for the academic year 2021/2022. Theosample was selectedoby randomksampling technique, class XIoIPA 6 as the experimentaloclass and class XI IPA 5 as the controloclass. The instrumentoused is a test of understanding mathematical concepts with essay uquestions. The hypothesis testoused is the U test. The results of data analysis at = 0.05 and P-value = 0.002 using the U test, it is known thatpthe understanding of mathematical concepts of students whooapply the Problem Based Learning model is better than students whooapply direct learning models in class XI IPA SMAN 1 Kecamatan  Lareh Sago Halaban.Keywords- uunderstanding  mathematical concepts, Problem Based Learning, direct learning